Management of cytotoxic chemotherapy-induced hand-foot syndrome - Johannes J.M. Kwakman; Yannick S. Elshot; Cornelis J.A. Punt; Miriam Koopman (Frontiers Media S.A., 2020)
Improvements in systemic cancer treatments have resulted in more patients surviving for prolonged periods of time on treatment. This has made treatment-related toxicity and quality of life concerns increasingly relevant. Hand-foot syndrome (HFS) is a common skin reaction to systemic therapy that should be anticipated with chemotherapeutic treatments such as pegylated liposomal doxorubicin, docetaxel, and fluoropyrimidines. In this review we discuss current knowledge of the diagnosis, incidence, pathogenesis, and management of hand-foot syndrome (HFS). Although HFS is not life threatening, it can cause significant discomfort and impairment of function, especially in elderly patients, and may seriously impact quality of life. The incidence of HFS is dependent on the chemotherapeutic drug used, the treatment schedule, and the median duration of treatment. Effective measures for prevention and treatment of HFS include systemic and topical treatments, dose reductions, and switching to other drugs in the same class that are associated with lower rates of HFS. These approaches allow patients to continue cancer treatment while reducing negative impacts on quality of life. Awareness and early recognition are important to ensure timely treatment and avoidance of dose reductions or treatment discontinuation. We provide useful recommendations to guide the management of HFS in clinical practice.